Actuation performance and versatility of photothermally driven organic crystals - Hasebe, Shodai; Hagiwara, Yuki; Asahi, Toru; Koshima, Hideko (Angewandte Chemie. International edition, 2025)
Photomechanical crystals exhibit mechanical motion upon light irradiation and may thus find applications as actuators. Over the last decades, many photomechanical organic crystals have been developed, commonly via photochemical reactions, particularly photoisomerization. However, photochemical crystal actuation is associated with several drawbacks, including a limited number of available crystals, slow actuation speed (<5 Hz), and narrow wavelength range (<550 nm). Such constraints have hindered the widespread use of crystals as actuation materials. In this minireview, we focus on crystal actuation by employing more universal physical phenomena (the photothermal effect and photothermally resonated natural vibration) and quantitatively evaluate actuation performance. Both mechanisms, particularly the latter, outperformed conventional photomechanical crystal activation in terms of both speed (maximum: 1,350 Hz) and the useful wavelength range (ultraviolet to near-infrared). The oscillation frequencies of the crystals exceeded those of polymers, efficiently filling the gap between soft and hard materials. Both the photothermal effect and natural vibration can actuate any crystal that absorbs light. These two versatile physical actuation mechanisms could expand 40 years of research on photomechanical crystals—which had been based on photochemical reactions—from the realm of chemistry into engineering and lead to their practical applications in actuators and soft robots.